Power Sharing in the Asia-Pacific - Benjamin Reilly (German Institute of Global and Area Studies (GIGA), 2014)
Executive power sharing has been practiced widely in the Asia-Pacific region, in both formal and informal ways. This paper examines the theory and practice of these various approaches to the sharing or dividing of governing power across the region. I look first at the broad issues of executive structure and the distinction between presidential and parliamentary systems across the region, at the divergent approaches taken to both formal and informal practices of executive inclusion, and at the empirical relationship between these variables and broader goals of political stability. Following this, I construct an "index of power sharing" to compare the horizontal sharing of powers across the region over time. Finally, I look at the experience of vertical power sharing via measures such as federalism, devolution, and autonomy.
Keywords: 300; power sharing; ethnicity; parties; elections; Asia